2024
DOI: 10.3390/hydrobiology3020005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Species of Leaves and Conditioning Time on Vernal Colonization by Temperate Lotic Isopods (Lirceus sp.)

Renee E. Heller,
Alison N. Stouffer,
Erika V. Iyengar

Abstract: While some streams have dense populations of aquatic detritivorous isopods, research on the colonization of leaf packs typically focuses on aquatic insects. To determine whether shifts in dominant local forest species might impact isopod populations, we placed leaf packs of red/sugar maple, American beech, and red oak on the substratum of riffles and pools in Cedar Creek (Allentown, PA, USA) in April 2019. We retrieved the packs after one week, re-deployed them, and re-collected them after two weeks of submers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
(104 reference statements)
1
0
1
Order By: Relevance
“…Despite the previously documented preference of isopods for fungal-colonized, rather than unconditioned, senescent leaf litter ( [23,57], and even studies in this same stream reach in [58]), neither of the types of isopods in our study increased their colonization densities over time. The pond isopods had greater colonization numbers in the first week, and the stream isopods did not alter their densities between weeks (Figure 2A).…”
Section: No Impact Of Leaf Skeletonizationcontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite the previously documented preference of isopods for fungal-colonized, rather than unconditioned, senescent leaf litter ( [23,57], and even studies in this same stream reach in [58]), neither of the types of isopods in our study increased their colonization densities over time. The pond isopods had greater colonization numbers in the first week, and the stream isopods did not alter their densities between weeks (Figure 2A).…”
Section: No Impact Of Leaf Skeletonizationcontrasting
confidence: 99%
“…Unfortunately, albeit perhaps not surprisingly, given the range of functional feeding groups and taxa we examined, there is a lack of a clear, consistent pattern of use of fresh leaf litter resources by stream and pond benthic macroinvertebrates. Similar to our findings, previous authors also reported variability in the impact of green leaves across invertebrate species [9,61], that relative amounts of consumption may be unrelated to nutritional and toughness differences among leaf species [19], and that exposure time, rather than leaf species, can be the main predictor of the degree of invertebrate colonization (e.g., [58,62]). Our current data suggest that allochthonous inputs of fresh summer leaves are often rapidly disintegrated (in little more than two weeks) in both lentic and lotic ecosystems, although some species (e.g., red oaks) retain their integrity substantially longer.…”
Section: Importance Of These Studiessupporting
confidence: 91%